Asian capital market development and integration: Challenges and opportunities (Oxford University Press, 2014)
This book analyses this dilemma and proposes that development of local bond markets and achieving greater market depth and interconnectedness is the best bet to prevent the reoccurrence of a currency crisis like 1997. It thus, assesses the progress achieved thus far in capital market integration in Asia, and compares it with its global peers.